Proteomic Analysis of Extracellular Vesicles Identifies CDCP1 as Critical Metastasis‐Related Glycoprotein in Lung Cancer - Lu Zhang; Yan Wu; Suntao Li; Miao Guo; Jiaqi Zhao; Chengxi Cao; Yan Zhang; Hua Xiao (Journal of Extracellular Vesicles, 2025)
Abstract Lung cancer is the most prevalent malignancy worldwide, with the majority of fatalities attributed to metastasis. Recent studies have demonstrated the pivotal role of extracellular vesicles (EVs) and glycoproteins in tumor progression. In this study, we compared the glycoproteome of EVs from 95C (low metastatic) and 95D (high metastatic) lung cancer cells to discover key targets in metastasis. Through coupling lectin affinity chromatography with quantitative proteomics, 1562 glycoproteins were identified. Compared to 95C EVs, 23 glycoproteins were significantly upregulated more than 20‐fold in 95D EVs, including CDCP1, TNC, NCAM2, and ITGA4. CUB‐domain containing protein 1 (CDCP1) was upregulated 143‐fold in 95D EVs, which is significantly correlated with poor prognosis of lung cancer patients in the TCGA database. We subsequently performed site‐specific glycoform profiling of CDCP1 using intact glycopeptide enrichment. Then we generated CDCP1 knockout (KO) 95D cell lines and revealed that the absence of CDCP1 reduced cell migration ability, which was also confirmed by EVs and cell co‐culture experiments. We further performed Ti4+‐IMAC‐based phosphoproteomic analysis to investigate the changes in signaling pathways in CDCP1 KO cell lines. 147 differentially expressed phosphoproteins were revealed. Verification experiments confirmed that the levels of phosphorylated SRC and JUN proteins, markers of ErbB signaling pathway, were decreased 5.5‐fold and 4.2‐fold, respectively. Glycosylation site mutagenesis identified N339 and N386 as critical functional determinants of CDCP1. Collectively, our data demonstrate that glycoprotein CDCP1 was selectively packed into EVs and potentially contributed to cancer metastasis, which is a critical target for anti‐metastasis research and cancer therapy.